(untitled) (Economic journal of Lesya Ukrainka Volyn National University, 2020)
Introduction. Nowadays, the most crucial case for corporations is sustainable corporate development. The request for the improvement of the competitiveness of businesses is projected into requests for individual managers. The requirements made on managers are called managerial competences. The skills most often recognized as vital to the manager’s success appear to be proper choices, given the discussion of the qualities needed for a skill to be sufficient. The potential of a manager is regarded as a basis for the rise of such skills. The successful manager’s performance is accomplished by the development of his potential. The primary source of such growth is management thinking. It includes management knowledge, skills, and experience by directors and has been identified as a significant factor to ensure that. Management thinking helps an organization to solve its difficulties related to asymmetries and uncertainty. Companies that integrate management thinking will create a competency that improves the abilities, knowledge, and behaviors managers need. The purpose of the article highlight challenges and recommends future investigation avenues that will expectedly further enrich management thinking. Results. It investigates how management thinking reveals itself in management practice in the corporation. The paper defines management thinking as the process of creating, implementing, integrating, and evaluating information to capture and control complex problems. It is also an essential form of creative activity. The publication develops the following types of thinking: theoretical and practical; reproductive and productive (creative); visual, verbal-logical, and visual-action; analytical and intuitive; divergent and convergent. Conclusions. Management thinking identifies, analyses, generalizes, synthesizes information, and helps make decisions based on professional knowledge and management experience.